7. ASSESSMENT OF THE EFFECTIVENESS, SAFETY AND CONSUMPTION OF DESFLURANE IN LOW-FLOW ANESTHESIA FOR OBSTETRICAL AND GYNECOLOGICAL SURGERY IN ADULTS AT NGHE AN OBSTETRICS AND PEDIATRIC HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objectives: (1) To evaluate the effectiveness of Desflurane in maintaining anesthesia in obstetric and gynecological surgery; (2) To evaluate adverse effects of Desflurane during and after surgery.Subjects and methods: A prospective clinical Descriptive study with a convenient sample size of 650 patients undergoing obstetric and gynecological surgery during the first 7 months of 2024. We used the method of induction of anesthesia with Propofol followed by maintenance of low-flow Desflurane anesthesia at 1 liter/minute for lower abdominal surgery (laparoscopic and open surgery) in 650 patients with the following.Results: Mean age of patients 46 ± 1.22 years; most patients had uterine fibroids (40.15%) and ectopic pregnancy (42.16%). Desflurane was maintained at an average level of 5.8 ± 0.42%; volume consumed was 48 ± 3.5 mL at a new gas flow of 1 liter/minute. Average patient heart rate 62-72 beats/minute. Blood pressure (systolic, diastolic, average) was within the allowable limits. SpO2, EtCO2 were within the normal limits. Bradycardia was found in 23 patients (3.54%); ventricular extrasystoles in 7 patients (1.08%); side effects of nausea and vomiting were 12 patients (1.85%); hallucinations were triggered in 32 patients (4.92%). No malignant hyperthermia or laryngospasm.Conclusion: The results of sleep maintenance were good for patients, maintaining SpO2 within good limits. Hemodynamics were relatively stable, without the use of vasoconstrictors or antihypertensive drugs to control blood pressure. Patients woke up quickly, the time to extubation (minutes) was short at 5.98 ± 0.23 minutes immediately after the inhalation anesthetic was turned off. The quality of consciousness was headed and clear, meeting the criteria for patients to recover normal memory. The low-flow maze line with a new gas flow of 1 liter/minute basically met the oxy deficiency and was not prioritized during the initial period of anesthesia maintenance.
Keywords: anesthesia; Desflurane; obstetrics and gynecology